Effects of LiF on the structure and properties of Ba0.85Ca0.15Zr0.1Ti0.9O3lead-free piezoelectric ceramics - Tan, Ivan Chee Kiang (2013)
Preparation of Ba0.85Ca0.15Zr0.1Ti0.9O3 (BCZT) lead-free piezoelectric ceramics with different amounts of LiF (BCZT-xLiF) was done, and the effects of the LiF doping on the phase transition behavior and the electrical properties of the resulting ceramic were investigated. The experimental results showed that the polymorphic rhombohedral-tetragonal phase transition temperature was found shifted toward room temperature with the Li doping. The study showed that BCZT lead-free piezoelectric ceramic with improved performance properties at room temperature can be achieved by shifting the polymorphic phase transition point nearer room temperature through the addition of LiF.